Heat Therapy to Reduce Chest-Pain Among Patients with Acute Coronary Syndromes (ACS): A Literature Review - Aan Nur'aeni; Yanny Trisyani; Donny Nurhamsyah; Oman Hendi; Rahmalia Amni; Vanny Leutualy; Gita Maya Sari; Nurlaeci Nurlaeci; Rika Winarni (Universitas Padjadjaran, 2020)
The main clinical manifestations of patients with Acute Coronary Syndrome (ACS) during the acute period is chest pain. Handling complaints of pain patients with ACS definitively done with medication; however, it is possible to do additional nonpharmacological therapies to optimize the results. Nonpharmacological treatment can be performed in various ways, one of them with heat therapy. This literature review aimed to determine the use of heat therapy as an additional nonpharmacological intervention in reducing the intensity of chest pain in patients with ACS. Four electronic databases were used to carry out systematic searches on articles, namely Proquest, Science Direct, Pubmed, and CINAHL-Ebsco. The combination of keywords was